2003
DOI: 10.1007/s00424-002-0904-z
|View full text |Cite
|
Sign up to set email alerts
|

Histaminergic modulation of the intact respiratory network of adult mice

Abstract: Histaminergic modulation of neuronal activity in the respiratory network was investigated under normoxic and hypoxic conditions in the working heart-brainstem preparation of adult mice. Systemic application of histamine, as well as the H-1 and H-3 receptor agonists 6-[2-(4-imidazolyl)ethylamino]- N-(4-trifluoromethylphenyl) heptanecarboxamide (HTMT) and imetit, 0.5-10 micro M, significantly increased the frequency of respiratory burst discharges. Dimaprit, an H-2 receptor agonist, had no effect on respiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 41 publications
4
26
0
Order By: Relevance
“…The central actions of HA are mediated by H 1 , H 2 and H 3 receptor subtypes, with H 1 and H 2 receptors mostly mediating excitatory postsynaptic actions and H 3 receptors, located on histaminergic and non-histaminergic endings, causing autoinhibition of the release and synthesis of HA and other neurotransmitters (Haas and Panula, 2003). A recent study has shown that HA modulates the medullary respiratory network mainly via H 1 receptors (Dutschmann et al, 2003). Although the histaminergic receptor subtypes controlling the activity of HMN remain to be determined, even with the current state of knowledge, our findings of the activating effect of HA might point the way towards a possible pharmacological approach for the treatment of OSA.…”
Section: Ha and Gg Muscle Activitymentioning
confidence: 99%
“…The central actions of HA are mediated by H 1 , H 2 and H 3 receptor subtypes, with H 1 and H 2 receptors mostly mediating excitatory postsynaptic actions and H 3 receptors, located on histaminergic and non-histaminergic endings, causing autoinhibition of the release and synthesis of HA and other neurotransmitters (Haas and Panula, 2003). A recent study has shown that HA modulates the medullary respiratory network mainly via H 1 receptors (Dutschmann et al, 2003). Although the histaminergic receptor subtypes controlling the activity of HMN remain to be determined, even with the current state of knowledge, our findings of the activating effect of HA might point the way towards a possible pharmacological approach for the treatment of OSA.…”
Section: Ha and Gg Muscle Activitymentioning
confidence: 99%
“…However, since hypocapnia was weak at 3-10 min after exposure, ventilation would still be sustained according to the metabolic demand in H1RKO mice. Histaminergic modulation during HVD is also illustrated by the evidence that a histamine H1 receptor antagonist reduces HVD for phrenic nerve activity after systemic administration in mice [14]. Thus H1-receptor modulation was obvious in the declined phase in response to poikilocapnic hypoxia.…”
Section: Ve (Ml/min/10g Bw)mentioning
confidence: 87%
“…Histamine is known as a functional neuromodulator that tonically acts on the respiratory neuron network and is further activated during hypoxia [14]. Histamine affects an inspiratory offswitch level during hypercapnia (5-9% CO 2 ) via H1 receptors [15].…”
mentioning
confidence: 99%
“…Further, excitatory transmitters are cholecystokinin, acting on CCK 1 receptors within one or more medullary or pontine respiratory groups, thyrotropin-releasing hormone, which induces bursting properties in neurons of the Ncl. tractus solitarius, and histamine, acting primarily on H1 receptors [14][15][16]. Primarily, inhibitory modulators are opioids and somatostatin [17].…”
Section: Introductionmentioning
confidence: 99%